2006
DOI: 10.1007/s10812-006-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Eye-safe radiation source based on an optical parametric oscillator

Abstract: We have studied an optical parametric oscillator (OPO) with an unstable telescopic cavity, placed inside the cavity of an actively Q-switched multimode Nd 3+ :KGW pump laser. We used a KTP crystal as the nonlinear medium for the OPO. We have compared the emission characteristics of OPOs with unstable telescopic and planar cavities. We have established that compared with the planar cavity, the unstable cavity reduces the OPO beam divergence and improves the spatial distribution of the radiation energy in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The results of this work and [20] show that the beam divergence for an OPO with an unstable cavity is reduced with a decrease in the divergence of the pump radiation, as for the case of OPOs with other types of cavities [26]. Since for a number of practical applications of eye-safe radiation sources based on OPOs, we are interested in not only the angular characteristics but also the energy characteristics of the radiation, the most acceptable method for reducing the divergence of the fundamental radiation is to increase the length of the cavity in the pump laser.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…The results of this work and [20] show that the beam divergence for an OPO with an unstable cavity is reduced with a decrease in the divergence of the pump radiation, as for the case of OPOs with other types of cavities [26]. Since for a number of practical applications of eye-safe radiation sources based on OPOs, we are interested in not only the angular characteristics but also the energy characteristics of the radiation, the most acceptable method for reducing the divergence of the fundamental radiation is to increase the length of the cavity in the pump laser.…”
mentioning
confidence: 64%
“…In this case, we focused our attention on both the temporal development of lasing and on the change in the spatial characteristics of the emission. To construct the pump laser, as in the previous paper [20] devoted to study of intracavity OPOs with multimode pumping, we used a potassium gadolinium tungstate crystal activated by neodymium ions: KGd(WO 4 ) 2 :Nd 3+ (KGW:Nd). Compared with other widely used laser media such as YAG:Nd 3+ , YLF:Nd 3+ , and YVO 4 :Nd 3+ [1][2][3][4][5][6][7][8][9][10][11][12][13], this laser material is characterized by a higher atomic concentration of the activator and relatively high lasing transition cross sections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present the feature analysis of extra-cavity OPO with LiNbO 3 resulted in a quantity of optical schemes [2][3][4][5][6][7]. The study of basic linear networks of OPO cavities [3,4] has shown that at satisfactory energy indictors the oscillator's divergence angle is rather high and runs up at the pumping energy increase.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of OPO confocal unstable cavity [7,8] provides for high quality of output beam at a divergence angle that is close to a diffraction one. However, such cavities are extra sensitive to disalignment and are suitable only to provide oscillation at a stable wavelength.…”
Section: Introductionmentioning
confidence: 99%